A Numerical Application of Ship Parametric Roll under Second Generation Stability Criteria - Cakici, Ferdi (CHAMBER MARINE ENGINEERS, 2019)
In this study, the parametric roll motion for the benchmark container ship form C11 is investigated by using the second generation stability criteria, which were intensively studied by IMO (International Maritime Organization). According to the IMO regulations, vulnerability criteria range between 1 and 3. While level 1 is only dependent on ship geometry and speed, level 3 is required to perform direct stability assessment with reliable robust software. The application of level 1 is considerably easy yet it is extremely conservative. Therefore, in the present study, level 2 application is performed that is less conservative than level 1 and easier than level 3. Parametric roll motion is analysed based on GM variation technique. Based on C2 assessment procedure which is calculated as an average of values of different Froude numbers and wave directions, it is found that the benchmark hull C11 was not vulnerable for the parametric roll resonance.
Keywords: Benchmark Hull C11; Parametric Roll; GM Variation Approach; Engineering; Transportation